Pet fiber reinforced sand performance under triaxial and plate load tests - Ferreira, José Wilson dos Santos (2021)
Annually, large amounts of waste Polyethylene Terephthalate (PET) bottles are discarded worldwide, although their properties can be useful in engineering works, such as soil improvement. Thus, the influence of PET fibers on sandy soil mechanical behavior was assessed in the present work. Consolidated-drained triaxial tests were performed using a 0.5% addition of 1.4 (SF-1) and 3.3 dtex fibers (SF-2). Afterward, plate load and slopes tests in the laboratory scale model were carried out for the most effective fiber. Overall, the inclusion of both fibers improved the stress-strain behavior, evident by greater absorbed strain energy in the reinforced soil. The insertion of 1.4 dtex PET fibers enhanced the internal friction angle of the soil from 31.9º to 44.3º, while a 29.7º value was obtained from 3.3 dtex fibers. Also, a cohesion intercept portion was identified in both composites, corresponding to 22.5 and 58.7 kPa for SF-1 and SF-2, respectively. The PET reinforcement reduced both vertical and horizontal deformation and altered the soil failure mechanism. The settlement reduction in fiber-reinforced sand is stress magnitude dependent, decreasing about 81% for stresses above 300 kPa, in which settlement of 125.3 mm from unreinforced sand was reduced to 23.6 mm by fiber insertion at 400 kPa. At the maximum comparable settlement, a 375.7% enhancement was seen in the bearing capacity, increasing from 240 kPa to 1141.6 kPa. In addition to a better understanding of soil-PET mixture, the results contribute to encouraging sustainable applications in engineering, such as embankment, shallow foundation, and retaining wall layers.